If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7r + 6r = -13 Combine like terms: 7r + 6r = 13r 13r = -13 Solving 13r = -13 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Divide each side by '13'. r = -1 Simplifying r = -1
| 14x+1=-2+8x+15 | | -14=b-2-8 | | 7x+23-2x=53 | | 1+2x-3x=9 | | -143=9n-8 | | 46=2w+16 | | 8s-11s+6=9 | | 5y+13+15y=43 | | b^2+11b+28b=0 | | 7=-5+6m | | 5(2x-4)=11x+14+9x | | -11=-10+n*16 | | 8.25z=155.5 | | z(2z-3)=17 | | 15w=1.25 | | 19y+5=45-9y | | 10x-20=20x+14 | | -3x+8=-4x+13 | | x^2-kx-3=0 | | 45+3x+10=180 | | 18x-25=11 | | y=2(y/3-1)+5 | | x-62=84 | | y=3ln(3) | | y+19=41 | | M-11.97=-3.97 | | 66=4m-18 | | y=4(y+4)-10 | | 66=4m-8 | | 108+36z=18z-18 | | z-7=47 | | 36=5+15 |